Immune reconstitution for the treatment of myasthenia gravis: the focus on cladribine - Rejdak, Konrad; Baranowski, Dariusz; Grieb, Paweł (Folia Neuropathologica, 2025)
Autoimmune diseases (AID) such as multiple sclerosis, rheumatoid arthritis, type 1 diabetes, inflammatory neuropathies, and some 100 other conditions, affect 5-10% of the global population, and their incidence is increasing, particularly in women. Among these, myasthenia gravis (MG) is a relatively rare but debilitating disease, which represents a prototype antibody-mediated autoimmune condition with well-studied pathogenesis. MG is a neuromuscular junction disorder marked clinically by fatigable muscle weakness and serologically by the presence of pathogenic autoantibodies. In MG pathological B- and T-cell subtypes are implicated, including memory B and plasma cells. In recent years there has been significant progress in the field of therapy, with several novel drugs introduced targeting major components of the pathogenetic pathway. However, there are still unmet needs in the treatment, especially the lack of a curative, upstream approach in contrast to the existing chronic downstream immunomodulatory actions. A nucleoside analog cladribine was primarily developed for the treatment of chronic leukaemias, in particular hairy cell leukaemia. For these indications, the injectable formulation of the drug was registered in 1997, and it has been manufactured in several countries since then. Later the oral formulation of cladribine (Mavenclad, Merck KGaA) was registered worldwide for use as immune reconstitution therapy (IRT) for relapsing multiple sclerosis. In this setting it has gained a strong position in the group of high-efficacy compounds, exerting long-term impact on the immune system. In a pilot clinical study, we found appreciable efficacy and safety profile of a short course of cladribine in MG. Herein, we present the design of a prospective, multicentre, randomised, controlled trial (RCT) using a parenteral preparation of cladribine in MG, currently ongoing in 6 clinical centres in Poland (EudraCT No. 2020-005762-34). In addition, we discuss the concept of immune reconstitution, which seems applicable for MG treatment.